Acupuncture Injection Combined with Electrokinetic Injection for Polydimethylsiloxane Microfluidic Devices - Ji Won Ha (Journal of Analytical Methods in Chemistry)
We recently reported acupuncture sample injection that leads to reproducible injection of nL-scale sample segments into a polydimethylsiloxane (PDMS) microchannel for microchip capillary electrophoresis. The advantages of the acupuncture injection in microchip capillary electrophoresis include capability of minimizing sample loss and voltage control hardware and capability of introducing sample plugs into any desired position of a microchannel. However, the challenge in the previous study was to achieve reproducible, pL-scale sample injections into PDMS microchannels. In the present study, we introduce an acupuncture injection technique combined with electrokinetic injection (AICEI) technique to inject pL-scale sample segments for microchip capillary electrophoresis. We carried out the capillary zone electrophoresis (CZE) separation of FITC and fluorescein, and the mixture of 10 μM FITC and 10 μM fluorescein was separated completely by using the AICEI method.